Model-Based Tracking Control of Nonlinear Systems - Jarzebowska, Elzbieta (Boca Raton : CRC Press, 2012)
Preface The book presents model-based control methods and techniques for nonlinear, specifically constrained, systems. It focuses on constructive control design methods with an emphasis on modeling constrained systems, generating dynamic control models, and designing tracking control algorithms for them. Actually, an active research geared by applications continues on dynamics and control of constrained systems. It is reflected by numerous research papers, monographs, and research reports. Many of them are listed at the end of each book chapter, but it is impossible to make the list complete. The book is not aimed at the survey of existing modeling, tracking, and stabilization design methods and algorithms. It offers some generalization of a tracking control design for constrained mechanical systems for which constraints can be of the programmed type and of arbitrary order. This generalization is developed throughout the book in accordance with the three main steps of a control design project, i.e., model building, controller design, and a controller implementation. The book content focuses on model building and, based upon this model that consists of the generalized programmed motion equations, on a presentation of new tracking control strategy architecture. The author would like to thank the editors at Taylor & Francis for their support in the book edition; Karol Pietrak, a Ph.D. candidate at Warsaw University of Technology, Warsaw, Poland, for excellent figure drawings in the book, and Maria Sanjuan-Janiec for the original book cover design--
1. Introduction -- 2. Dynamics modeling of constrained systems -- 3. Introduction to nonlinear control theory -- 4. Stabilization strategies for nonlinear systems -- 5. Model-based tracking control of nonlinear systems -- 6. Path following strategies for nonlinear systems -- 7. Model reference tracking control of high order nonholonomic systems -- 8. Concluding remarks.
Keywords: Nonlinear systems -- Automatic control -- Mathematics; Automatic tracking -- Mathematics; Nonlinear systems -- Mathematical models; Control theory; Electronic books